Supermacroporous poly (vinyl alcohol)-carboxylmethyl chitosan-poly (ethylene glycol) scaffold: an in vitro and in vivo pre-assessments for cartilage tissue engineering - Lee, S.Y.; Wee, A.S.; Lim, C.K.; Abbas, A.A.; Selvaratnam, L.; Merican, A.M.; Ahmad, T.S.; Kamarul, Tunku (2013)
This study aims to pre-assess the in vitro and in vivo biocompatibility of poly(vinyl alcohol)-carboxylmethyl-chitosan-poly(ethylene glycol) (PCP) scaffold. PCP was lyophilised to create supermacroporous structures. 3-(4, 5-dimethyl-thiazol-2yl)-2, 5-diphenyltetrazolium bromide (MTT) assay and immunohistochemistry (IHC) were used to evaluate the effectiveness of PCP scaffolds for chondrocytes attachment and proliferation. The ultrastructural was assessed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Extracellular matrix (ECM) formation was evaluated using collagen type-II staining, glycosaminoglycan (GAG) and collagen assays. Histological analysis was conducted on 3-week implanted SpragueâDawley rats. The MTT, IHC, SEM and TEM analyses confirm that PCP scaffolds promoted cell attachment and proliferation in vitro. The chondrocyte-PCP constructs secreted GAG and collagen type-II, both increased significantly from day-14 to day-28 (P < 0.05). PCP scaffolds did not elicit any adverse effects on the host tissue, but were partially degraded. These results suggest that supermacroporous PCP is a biocompatible scaffold for clinical applications.